2019
DOI: 10.1080/19476337.2019.1575908
|View full text |Cite
|
Sign up to set email alerts
|

Purified avocado seed acetogenins: Antimicrobial spectrum and complete inhibition of Listeria monocytogenes in a refrigerated food matrix

Abstract: Avocado fruit contains lipid derivatives with antimicrobial properties called acetogenins. In this study, antimicrobial spectrum of purified acetogenins was characterized. Additionally, eight Grampositive bacteria were exposed to commercial food preservatives (Nisaplin® and Mirenat®) for comparison. Acetogenins were also added to a food system containing meat, inoculated with Listeria monocytogenes and stored at 20°C and 4°C. Avocado seed extract (Avosafe®) contained 71.3% w/w total acetogenins, its main compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 50 publications
0
22
0
3
Order By: Relevance
“…Therefore, the test with L. monocytogenes was successful, decreasing initial growth of bacteria. In addition, the results showed a significant inhibition activity against Gram-positive and Gram-negative strains [110,111].…”
Section: Drugs and Bioactive Compoundsmentioning
confidence: 89%
“…Therefore, the test with L. monocytogenes was successful, decreasing initial growth of bacteria. In addition, the results showed a significant inhibition activity against Gram-positive and Gram-negative strains [110,111].…”
Section: Drugs and Bioactive Compoundsmentioning
confidence: 89%
“…Studies on the chemical characterization of the acetogenin-enriched extract confirmed the chemical structures of seven acetogenins as present in the enriched avocado seed extract and 21.50 ± 1.87% w / w of solids remained to be characterized [6]. Prior studies also documented that acetogenins were stable under relevant food processing conditions (temperature, pressure, salt, pH), and were capable of controlling C. sporogenes endospore germination [5] and Listeria monocytogenes outgrowth [6,7] in both laboratory culture media and within food systems that contained meat.…”
Section: Introductionmentioning
confidence: 81%
“…This family of phytochemicals has been reported to be exclusively present in species of the genus Persea (family: Lauraceae) [1] and are found in different varieties and tissues (peel, pulp, and seed [2], as well as in leaves [3]) of avocado fruit ( Persea americana Mill.). Of special interest to the food industry is their bioactivity as antimicrobial additives due to their ability to inhibit germination of bacterial endospores [4,5] and to act as listericidal additives [6,7]. Initial studies on their ability to inhibit bacterial endospores were performed using acetogenin-enriched extracts purified in a laboratory setting using bioassay-guided isolation [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RESUMEN: El propósito de esta investigación fue analizar las potencialidades del aceite de la semilla del aguacate para su aprovechamiento. Esta investigación tuvo un enfoque cualitativo de tipo descriptivo con diseño documental fundamentada en autores como Almanza, Navarro & Ruiz, 2019;Cid et al, 2021;Coello & Saltos, 2020;Da silva & Deschamps, 2020;Del Castillo et al, 2021;Higuera, Zuluaga & Rodríguez, 2021;Martínez & Santana, 2019;Villarreal et al, 2019;Zabala, 2020; empleando diferentes bases de datos como Sciencedirect, Scielo, Scopus, Redalyc, Google Academic, entre otras. Se encontraron diversos metabolitos secundarios que le otorgan propiedades antioxidantes, antiinflamatorias, cardiovasculares, metabólicas, por lo que se considera que podría ser utilizada en la fabricación de medicamentos, alimentos y cosméticos, principalmente.…”
Section: Apresentaçãounclassified